Three-dimensional core-shell alginate microsphere for cancer hypoxia simulation in vitro - Yejiao Ruan; Lingyun He; Jiamin Chen; Jinfeng Wang; Shujing Zhao; Xiaoling Guo; Yao Xie; Zhenzhai Cai; Xian Shen; Chao Li (Frontiers in Bioengineering and Biotechnology, 2023)
Hypoxia is one of the major causes of cancer resistance and metastasis. Currently, it is still lack of convenient ways to simulate the in vivo hypoxic tumor microenvironment (TME) under normoxia in vitro. In this study, based on multi-polymerized alginate, we established a three-dimensional culture system with a core-shell structure (3d-ACS), which prevents oxygen diffusion to a certain extent, thereby simulating the hypoxic TME in vivo. The cell activity, hypoxia inducible factor (HIF) expression, drug resistance, and the related gene and protein changes of the gastric cancer (GC) cells were investigated in vitro and in vivo. The results demonstrated that the GC cells formed organoid-like structures in the 3d-ACS and manifested more aggressive growth and decreased drug responses. Our study provides an accessible hypoxia platform in the laboratory with moderate configuration and it may be applied in studies of the hypoxia-induced drug resistances and other preclinical fields.